Employee Performance in the Spatial Planning Department of Public Works and Spatial Planning in Karawang Regency in Optimizing Public Services - Kirana Puspamurty; Dadan Kurniansyah; Gun Gun Gumilar (Peneliti.net, 2022)
This study aims to examine and analyze the performance of employees in the Spatial Planning Department of Public Works and Spatial Planning in Karawang Regency in optimizing public services. This study uses a qualitative descriptive approach with the data collection technique used is triangulation including interviews, observation and documentation, then analyzed through the Miles and Huberman model which includes reduction, presentation and drawing conclusions. The discussion of this research is reviewed using Mitchell's performance theory (Sedarmayanti, 2001:51) where there are five dimensions namely work quality, timeliness, initiative, ability and communication. The results of this study indicate that the performance of employees in the Spatial Planning Division of the DPUPR Karawang in quality shows good results with a lot of creativity that appears, but in punctuality there are still many who arrive late, the initiative is very high with a fairly agile work response, the ability of the employees There is no doubt about the DPUPR and there is a close relationship between employees in terms of communication.